Mental health help-seeking among Korean men: the influence of stigma, masculine norms, and face - Soomin Kim; Dongil Kim (BMC Psychology)
Abstract Background Previous studies have found that Asians and men are more susceptible to the stigma and stereotypes associated with mental illness. This social perception makes it difficult for Korean men to seek professional psychological help even when they desperately need it. The primary objectives of this study were to investigate barriers to mental health help-seeking among Korean men and to identify the role of sociocultural factors. Methods A total of 341 Korean men aged 19 to 59 years participated in an online survey, which included questionnaires on loss of face, self-stigma of seeking help, attitudes toward seeking professional psychological help, and conformity to masculine norms. Structural Equation Modeling was used to explore the relationships among these variables. Results The results revealed that loss of face indirectly affected attitudes toward seeking professional psychological help (ATSPPH) through its mediating effect on self-stigma. Loss of face did not directly influence ATSPPH. Furthermore, conformity to masculine norms negatively affected ATSPPH, and self-stigma mediated this relationship. Conclusion These findings highlight the importance of understanding the influence of sociocultural factors in encouraging Korean men to seek help. The ultimate goal is to foster a social environment that encourages open discussion about mental illness, masculinity, and Asian values.